2016
DOI: 10.1371/journal.pone.0158021
|View full text |Cite|
|
Sign up to set email alerts
|

CD90 and CD24 Co-Expression Is Associated with Pancreatic Intraepithelial Neoplasias

Abstract: Thy-1 (CD90) has been shown to be a potential marker for several different types of cancer. However, reports on CD90 expression in pancreatic intraepithelial neoplasia (PanIN) lesions are still limited where PanINs are the most important precursor lesion of pancreatic ductal adenocarcinoma (PDAC). Herein, we investigate candidate markers for PanIN lesions by examining the distribution and trend of CD90 and CD24 expression as well as their co-expression in various stages of PanINs. Thirty cases of PanINs, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
3
6
0
Order By: Relevance
“…Various studies have reported that CD24 expression was highly correlated with the progression of pancreatic cancer [20, 22]. Our previous IHC studies showed that CD24 expression was restricted to the membrane of malignant ducts in PDACs [20] and ductal epithelial cells in PanINs [34]. In this study, abundant ANXA10 expression was also predominantly present in ductal epithelial cells of PanINs and IPMNs and malignant ducts of PDACs.…”
Section: Discussionsupporting
confidence: 64%
“…Various studies have reported that CD24 expression was highly correlated with the progression of pancreatic cancer [20, 22]. Our previous IHC studies showed that CD24 expression was restricted to the membrane of malignant ducts in PDACs [20] and ductal epithelial cells in PanINs [34]. In this study, abundant ANXA10 expression was also predominantly present in ductal epithelial cells of PanINs and IPMNs and malignant ducts of PDACs.…”
Section: Discussionsupporting
confidence: 64%
“…In addition, our group has identified and validated Thy1 as a novel, highly specific neo-angiogenesis marker in patients with PDAC (Foygel et al 2013). This has been confirmed by a subsequent independent study that reported significant overexpression of Thy1 in patients with PDAC compared with those with a normal pancreas and chronic pancreatitis (Zhu et al 2014;Pei et al 2016). Abou-Elkacem et al (2018) also used a clinically translatable dual human and murine Thy1-binding single-chain variable fragment (scFv) conjugated to MBs to illustrate the feasibility of in vivo Thy1-targeted ultrasound molecular imaging of PDAC in two animal models, a human PDAC xenograft and a transgenic mouse model (Fig.…”
Section: Molecular Imaging In Oncologysupporting
confidence: 52%
“…Furthermore, similar studies have also revealed the crucial role THY1 plays in the development and progression of glioblastoma multiforme CSCs, which enlightened the further studies that THY1 might be an appropriate target for anti-tumor vasculature [42]. Not only does THY1 act as a candidate marker for cancer therapy but THY1 also is involved in cell adhesion, migration and fibrosis [6]. It was easier for fibroblasts to transform into myofibroblasts by positively expressing THY1, a versatile regulator of cellular processes [43].…”
Section: Discussionmentioning
confidence: 89%
“…Gene expression is one of the most fundamental processes of life, including the transcription, translation and turnover of messenger RNAs (mRNAs) and proteins [5]. Thymocyte differentiation antigen-1 (THY1) is a highly conserved glycoprotein belonging to the immunoglobulin superfamily [6]. THY1, also known as CD90, has been previously demonstrated as a cancer biomarker [7].…”
Section: Introductionmentioning
confidence: 99%